CHALLENGES TO CIRCULATION ON THE BORDER BETWEEN BRAZIL AND FRENCH GUIANA (FRANCE) - Silva, Gutemberg de Vilhena; Granger, Stephane; Le Tourneu, François Michel (Mercator, 2019)
Brazil and France share a long border across the Oiapoque river, located in the Amazon. This paper tries to evaluate how actions undertaken since the establishment of the international limit, in 1900, have shaped and re-shaped systems of regional circulation and trade in this river basin. Using both a bibliographical review and information derived from fieldwork, we conclude that three major changes have occurred recently: (i) the previously hegemonic fluvial circulation is now in competition with terrestrial circulation; ii) previously dominant local informal rules have been downplayed in favor of international rules; and iii) a contradiction has appeared in bilateral relations: the official discourse focused on “integration” values an increase of the interface between the two river banks while in practice a decrease in interactions and a tightening of the rules of circulation seems to be happening. Keywords : Regional Circulation. Brazil. French Guiana (France).